MODALIDADES DE TRADUÇÃO E OPERAÇÕES ENUNCIATIVAS: O CASO DO MARCADOR LÉXICOGRAMATICAL UM E SUAS TRADUÇÕES PARA O FRANCÊS - Zavaglia, Adriana (Intercâmbio, 2010)
This work aims at presenting some thoughts about the relation between translation modalities (Aubert, 1998) and enunciative operations of language (Culioli, 2000) in specific co-texts and contexts from the occurrences of the marker UM in a Sagarana’s novel and its translations to French.